Towards a Land Titling Framework for Improving Rural Livelihoods: FIG Working Week 2020, Smart surveyors for land and water management; Amsterdam, the Netherlands, 10–14 May 2020 - Muchechetere, Paul; Kurwakumire, Edward (2022)
The continuum of rights model developed by UN-Habitat describes different forms of relationships that mankind has with land. These rights range from the informal to formal continuum. It is the less formal rights that are of major concern especially in the developing world as they are in most cases neither officially registered nor documented. This brings forth various land administration problems to include difficulty in managing natural disasters and land resources. The absence of land registration in customary tenure areas has resulted in research in land titling as a method to move informal tenure arrangements to the formal domains and hence with the assumption that land titling improves land tenure security. Whether or not land titling is working has varied opinions in academic literature. The aim of this study is to determine factors influencing the misalignment between land titling, land tenure security and the improvement of the quality of life of communities. The second aim is to design a land titling framework that addresses these misalignments. This study reviews literature on land titling with land tenure security as the unit of analysis. We critically analyse the relationship between land titling and land tenure security including the extent of this relationship based on a systematic literature review. Based on issues in land titling for customary and land resettlement areas that have been presented in academic literature, a framework for land titling is proposed. The framework addresses sustainable development goals 1 and 2 as it focuses on improving rural livelihoods through tenure security and community empowerment. Land tenure reform is a public infrastructure and should not be implemented in isolation of other developmental activities. The land titling policy framework should be aligned with the development goals of a national and spatial development framework at municipality level to ensure sustainability.